Estimulación sensorial y su incidencia en el desarrollo de la coordinación visomotriz de los niños de 2 y 3 años de la Unidad Educativa Particular Gregoriano de la ciudad de Guayaquil - Quimiz Pincay, Martha Mercedes (2016)
The purpose of this research work refers to sensory stimulation and its impact on the development of hand-eye coordination in children 2 and 3 years of the Special Education Unit Gregorian. Sensory stimulation is very important in the early years of life of infants, early childhood is where children discover and explore their environment through the senses, getting all the sensory stimuli that will provide, since that is the propitious way to acquire further development of all its capabilities. It is therefore necessary to stimulate the senses in the child thus contributing to the optimum development of their hand-eye coordination. The methodology used is descriptive in nature, the survey instrument to principals, teachers and parents research was applied, the observation technique was also used for children 2 and 3 years through the applied instruments the importance of observed stimulate the senses in the infant. This research work proposes to teaching a different and active way of working with children in the classroom through learning environments in which they stimulate their senses and be builders of their own knowledge, as well as, it is proposed to working parents with family schedules saturdays and fun, through which to share and enjoy daily activities with toddler at the same time to be stimulated….